STRATEGI PEMBELAJARAN DALAM MENINGKATKAN INTERAKSI EDUKATIF PEMBELAJARAN BAHASA PADA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Yunanda Ersal; Hermandra Hermandra; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of the research to describe the educative interaction and dominant learning strategy applied by lecturers to increase the activity Japanese Educations Language students of Riau University. The subjects chosen in this study are communicative courses, Kaiwa and Choukai 6 and Bijinesu Nihongo. The study used qualitative approach with describe method. The object of the study was the lecturer who teaches the subject. The technique of collecting data used ware observations technique and interview technique. The results of the research explain that the tendency of categories that appear in Kaiwa and Choukai 6 and Bijinesu Nihongo learning have similarities. Based on seven categories of Brown (BIAS), tendency of categories appear is pupil responses category. Most of the students prefer in speaking activity both in giving comment and asking, this is in line with the applied learning strategy by the lecturers is interactive learning strategy. Based on the dominant learning strategy applied, it has positive influence on student activity while studying and use Japanese language.Key Words: Learning Strategies, Educative Interaction, Language Learning